Actualization of Da'wah And Communication Values in the Nilekka Tradition Among The Makassar Tribe In Makassar City - Rintoh Rintoh; Nurdin Nurdin; Akbar Ista; Hikmawati Sultani; Rawati Rawati (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to examine the actualization of da'wah and communication values in the Nilekka tradition among the Makassar ethnic community in Makassar City. This research employs a qualitative method with a descriptive-analytical approach and was conducted in Makassar City, South Sulawesi. Research participants were selected using a purposive sampling technique, involving traditional leaders, religious leaders, and married couples who had recently undergone the Nilekka procession. Data were collected through participant observation, interviews, and documentation studies, and subsequently analyzed using the interactive qualitative data analysis model. The findings reveal that the Nilekka tradition functions as a medium of cultural da'wah communication that integrates customary practices with Islamic law. The da'wah messages conveyed encompass aspects of aqidah (Islamic creed), reflected in the intention of worship and submission to divine destiny; aspects of sharia, manifested through the public announcement of marriage and the transition of mahram relationships; and aspects of akhlaq (Islamic morality), expressed through respect for in-laws and the strengthening of social bonds (silaturahmi). These messages are articulated through structured communication patterns, namely symbolic communication in the handover of pakmattoang and pannimbaranngi, verbal communication through pappaseng advice and pakkiok bunting poetry, and non-verbal communication through the modification of the traditional Baju Bodo attire complemented by the wearing of the hijab. Therefore, the Nilekka tradition demonstrates a strong capacity to synergize with religious teachings without losing its essential values, enabling it to remain preserved as a cultural heritage.